THE RELATIONSHIP BETWEEN EDUCATION ON COMPLEMENTARY FEEDING OF BREAST MILK MADE FROM LOCAL FOODS AND THE KNOWLEDGE AND MOTIVATION OF TODDLER MOTHERS AS A STRATEGY TO PREVENT STUNTING IN 3T AREAS - Berhimpong, Vivi Meiti; Bawaeda, Olivia; Sangge, Irma Suryani (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
Introduction: Stunting is a chronic malnutrition problem caused by inadequate nutritional intake over a long period. Mothers play an important role in the family to overcome nutritional problems, especially those related to parenting and family nutrition. Objective: The purpose of this study was to determine the relationship between education on complementary foods for breast milk made from local foods and the knowledge and motivation of mothers of toddlers as a strategy in preventing stunting in the 3T area. Method: Quantitative correlational research design with a cross-sectional approach. The number of research samples was 50 mothers with a simple purposive sampling technique. Results: The results showed a p-value = 0.001 which was smaller than α (<0.05). The correlation coefficient value (r = 0.465) shows that there is a relationship between education on complementary foods for breast milk made from local foods and the knowledge of mothers of toddlers in efforts to prevent stunting also the p-value = 0.000 which is smaller than α (<0.05) The correlation coefficient value (r = 0.554) shows that there is a relationship between the duration of education on complementary foods for breast milk made from local foods and the motivation of mothers of toddlers in efforts to prevent stunting. Conclusion: there is a relationship between education on complementary foods for breast milk made from local foods and the knowledge and motivation of mothers of toddlers as a strategy in preventing stunting in the 3T area